UPAYA PENANGANAN BULLYING DI SMP AR RAHMAH ISLAMIC BOARDING SCHOOL MALANG - Priyanto; Nur Huda (el Hakim Press, 2023)
This study aims to find out efforts made in Ar Rahmah Secondary Islamic boarding school to handle bullying. The research uses a qualitative descriptive approach methode. In this study, the authors acted as data collectors and as active instruments. Subject of this study were teacher board and some student using purposive and snowball sampling. Datas analized by reduction, displaying and conclusion drawing. Datas validity checked by triangulation of trust, dependence, and certainty. Study concluded there some attemps to deal with and reduce bullying in Ar Rahmah Secondary Islamic boarding school. The attemps derived to three acts. 1) Precaution act: debriefing about bullying, providing examples, 2) Monitoring act: Identifying, receiving reports, collecting information, 3) Enforcement act: providing services, mediating settlements between perpetrators and victims, and enforcing sanctions for bullies.